Hazard identification and risk assessment and control (IPERC) in the Miniplant of the spinning and weaving Faculty of Industrial Engineering - UNMSM - Medina Escudero, Ana María (2016)
Knowledge of production processes is a guarantee in detecting existing real risk and is why as part of the professional academic training of students of Textile Engineering are trained in different textile processes. For the process of spinning and weaving fiber specialist as the card, the draw frame, the spinner and knitter who is in the Mini plant spinning and weaving machinery Faculty it is required; and a suitable training to prevent injury and on safety measures when handling them. In that sense, this article aims to identify hazards and assess risks and control measures (IPERC) in la Miniplanta de Hilandería y Tejeduría de la Facultad de Ingeniería Industrial de la UNMSM using the methodology suggested by the Ministerio del Trabajo y Promoción del Empleo (MTPE)) and also meet one of the principles of the Law on Safety and Health at Work, Law 29783, which is the principle of prevention.